English English - Anni Rachmayani; Didin Nuruddin Hidayat; Alek Alek (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study aims to explore the transitivity process in elementary school students' opinion essays on environmental issues in the city. This study is a descriptive qualitative research that uses Fairclough's (1989, 2010) Critical Discourse Analysis (CDA) framework to analyze the data and Halliday's transitivity theory from Systemic Functional Linguistics (SFL) to analyze the students' opinion essays. The research findings show that the most dominant Transitivity Process is Material Process, where 29 clauses are found in female essays and 10 clauses in male essays, followed by Relational Attributive, Mental, and Existential Attributive Processes. Meanwhile, Behavioral and Verbal Processes did not appear in the writings. Female students produce more writing than male students. Then, based on Fairclough's theory, students use Material Process to narrate environmental issues in the form of physical objects and real actions; Existential Process to describe conditions and things that happen and exist in the city; Relational Attributive Process expresses more specific information about activities by explaining the characteristics of participants and circumstances; and Mental Process is used to describe how students feel and see environmental issues based on their perspectives and experiences as citizens.